STRATEGI KOMUNIKASI BMKG DALAM DIFUSI INOVASI MITIGASI BENCANA ALAM MENGGUNAKAN MEME DAN VTUBER MELALUI INSTAGRAM @STAGEOF.GOWA - Fadil Chambali Mukti Wibowo; Julyanto Ekantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
Disaster mitigation is a crucial aspect of building community preparedness in facing increasingly complex disaster risks. The diffusion of disaster mitigation innovations is necessary as a structured and consistent communication process to disseminate public understanding of potential hazards and promote the adoption of innovative and effective preventive measures. This innovation diffusion not only functions as an information delivery tool but also fosters awareness and encourages active public participation in adopting appropriate technologies, strategies, and behaviors in the digital age.This study aims to analyze the communication strategy of the Meteorology, Climatology, and Geophysics Agency (BMKG) through the Instagram account @stageof.gowa, using a creative approach with meme content and VTuber characters as educational media. This research uses a qualitative method with data collection techniques including in-depth interviews, observation, and documentation. It adopts Everett M. Rogers' Diffusion of Innovation theory, focusing on three main aspects: the elements of innovation, the stages of the innovation-decision process, and the characteristics of innovation.The results show that this creative strategy effectively captures public attention and enhances disaster awareness, especially among younger audiences. It also creates adaptive communication patterns and expands outreach, aligning with the digital behavior of today’s society.